AA Amyloid Deposition in the Central and Peripheral Nervous Systems in Flamingos. Issue 5 (September 2020) - Ono, Ayumi; Nakayama, Yumi; Inoue, Maki; Yanai, Tokuma; Murakami, Tomoaki
AA amyloidosis is characterized by amyloid deposition in systemic organs, but amyloid deposition in the central nervous system (CNS) or peripheral nervous system (PNS) is rare. In this study, AA amyloidosis was observed in 31 of 48 flamingos that died at a Japanese zoo. Almost all cases developed AA amyloidosis secondary to inflammatory diseases such as enteritis. Affected flamingos had AA amyloid deposition around blood vessels in periventricular white matter of the brain and in peripheral nerves. In addition, cerebral Aβ amyloidosis was observed in one of the 31 cases with AA amyloidosis. In conclusion, flamingos in the zoo commonly developed systemic amyloidosis with frequent amyloid deposition in the CNS and PNS, which seems to be a unique distribution in this avian species. Comparative pathological analyses in flamingos may help elucidate the pathogenesis of amyloid neuropathy.